IDENTIFIKASI MAKROSKOPIK DAN MIKROSKOPIK SEDIAAN JAMU ASAM URAT YANG BEREDAR DI KOTA MAKASSAR - Handayani, Virsa (Jurnal Ilmiah As-Syifaa, 2011)
Was done research about pharmacognostic identification from muscle acid medicinal herbs that circulating at Makassar city., with aim to get pharmacognostic’s data from medicinal herbs of muscle acid that circulating at Makassar, for security in consuming. This research covers macroscopic and microscopic. On microscopic test medicinal herbs powder A, B dan C there are endosperm, parenkim with sekresi cell, fiber and calsium oksalat. From both offabove sample,really contains Zingiberis Rhizoma, Phaleria macrocarpa andyy `Piper nigrumKey word : Makroskopic, mikroskopic, muscle acid medicinal herbs